2007
DOI: 10.1099/vir.0.82839-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistent memory CD4+ and CD8+ T-cell responses in recovered severe acute respiratory syndrome (SARS) patients to SARS coronavirus M antigen

Abstract: The membrane (M) protein of severe acute respiratory syndrome coronavirus (SARS-CoV) is a major glycoprotein with multiple biological functions. In this study, we found that memory T cells against M protein were persistent in recovered SARS patients by detecting gamma interferon (IFN-γ) production using ELISA and ELISpot assays. Flow cytometric analysis showed that both CD4+ and CD8+ T cells were involved in cellular responses to SARS-CoV M antigen. Furthermore, memory CD8+ T cells displayed an effector memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 30 publications
5
51
0
Order By: Relevance
“…The terminally differentiated phenotype exhibited by Vd1 T cells in transplant recipients parallels the phenotypic characteristics of effector memory RA ab CD8+ T cells (T EMRA ) [23] found in the context of persistent viral infections [24]. While we lack data on the specificity of the expanded cd T cells for our patients, their phenotypic traits are very similar to expanded cd T cell subset, CMV specific, recently identified in kidney recipients [25].…”
Section: Vd1 T Cells [%(Sem)] Vd2 T Cells [%(Sem)]supporting
confidence: 67%
“…The terminally differentiated phenotype exhibited by Vd1 T cells in transplant recipients parallels the phenotypic characteristics of effector memory RA ab CD8+ T cells (T EMRA ) [23] found in the context of persistent viral infections [24]. While we lack data on the specificity of the expanded cd T cells for our patients, their phenotypic traits are very similar to expanded cd T cell subset, CMV specific, recently identified in kidney recipients [25].…”
Section: Vd1 T Cells [%(Sem)] Vd2 T Cells [%(Sem)]supporting
confidence: 67%
“…A recent study using MA15-infected mouse models suggested that age-dependent increases of prostaglandin D2 expression in the lung may be associated with impaired immune response (Zhao et al, 2011). Retrospective analyses of recovered SARS patients suggests that patients who recovered from SARS possessed specific acquired immunity based on both T and B cells (Yang et al, 2006(Yang et al, , 2007Li et al, 2008;Fan et al, 2009). Notably, most patients who recover from SARS had elevated and sustained levels of neutralizing Abs, and patients with longer illnesses exhibited lower levels of neutralizing Abs than did patients with shorter durations of illness (Temperton et al, 2005;Ho et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The development of an effective treatment strategy for SARS cases will require clarifying the precise mechanisms by which host immune responses control SARS-CoV infection. Cumulative evidence suggests that patients who recovered from SARS possessed specific acquired immunity based on both T and B cells (Yang et al, 2006(Yang et al, , 2007Li et al, 2008;Fan et al, 2009). However, the effector cells or molecules that act to eliminate SARS-CoV during the acute phase of the infection remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although whether the memory T-cell response is sufficient to protect from reinfection requires further investigation, it has been suggested that a more robust CTL response contributes to protection against SARS-CoV in mice Chen et al, 2010a;Zhao et al, 2010a). 2009; Peng et al, 2006;Yang et al, 2006Yang et al, , 2007. Unlike waning serum antibody levels in patients, CTL responses against the S and N proteins can still be detected from the PBMCs of recovered SARS patients 1, 2, 4, 6, and even >10 years post-infection (Da Guan et al, 2015;Ng et al, 2016;Oh et al, 2011;Tang et al, 2011).…”
Section: T-cell Immunity To Sars-covmentioning
confidence: 99%